Characteristics of acoustic signals from lightning using a microphone array observation system. (August 2019) - Hazmi, A; Emeraldi, P; Hamid, M I
Abstract: The acoustic signals of thunder provide information on the lightning channel, such as frequency, power spectra density, and images. In this study, to analyze the frequency variation in acoustic signals of thunder and to reconstruct the 3D lightning channel imaging, the short time Fourier transform (STFT) and differential time of arrival (DTOA) methods were used. The results showed that the frequency for four microphones varied from 4.88 Hz to 175.78 Hz. Furthermore, the range of power spectra density values for the four microphones was between -0.59 dB/Hz and -28.31 dB/Hz. This system can reconstruct 3D lightning channel imaging.